Bigheaded Carp-Based Meal as a Sustainable and Natural Source of Methionine in Feed for Ecological and Organic Poultry Production. (6th August 2019) - Upadhyaya, I; Arsi, K; Fanatico, A; Wagle, B R; Shrestha, S; Upadhyay, A; Coon, C N; Schlumbohm, M; Trushenski, J; Owens-Hanning, C; Riaz, M N; Farnell, M B; et al.
SUMMARY: High-quality protein feeds are needed in ecological and organic poultry production. Feeds that are rich in methionine (MET ) are particularly important because synthetic amino acids are generally prohibited in organic livestock production. Bigheaded carp present an opportunity as feed because they are an invasive fish species that are high in protein and MET. A carp-based meal (CBM ) was prepared using innovative dry extrusion, and proximate analysis and nutritional analyses were conducted. The digestible amino acids and true metabolizable energy (TMEn ) of the CBM were determined using a colony of cecetomized adult roosters. Starter and grower diets were formulated with CBM and tested in a broiler feeding trial. Diets were high overall in protein, but formulated without synthetic MET. Day-old chicks were randomly assigned to pens of 30 chicks belonging to 1 of 2 treatments (CBM or control containing synthetic MET), with 8 replications. Body weights, feed intake, and feed conversion ratio (FCR ) for starter (0–21 d), grower (22–42 d), and overall periods (0–42 d) were analyzed using 1-way ANOVA. The weight gains, feed intake, and FCR did not differ between treatments ( P > 0.05) for the overall period (0–42 d). The results indicate that invasive bigheaded carp can be harvested and dry extruded into a novel meal, providing not only a natural and sustainable source of MET, but also an environmental service for damaged aquatic ecosystems in the U.S.